2016
DOI: 10.3892/ol.2016.5142
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of estrogen receptor β in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the fifth most common cancer in the world. Although multimodal and targeted therapy is now used in therapeutic procedures, the survival of patients with HNSCC has remained unchanged over the last 30 years. A number of studies have demonstrated that the increased expression of intranuclear ERβ in breast, lung and colon cancer is a favorable prognostic marker associated with higher survival rates. However, the clinical significance of sex hormone receptors in HNSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The proportion of ERα positive breast cancer incidence relative to the total diagnoses is similar for patients in the United States and Northern Israel 86,87 ; however, our data suggest that ERβ positive cancer incidence may be more regionally localized. Other studies have reported high variability of ERβ expression in laryngeal cancer samples, similar to the trends we observed in our samples 88 . It is important to note that although western blots were conducted in a centralized lab, our samples were originally fixed and processed at two different institutions, which could have caused "batch processing effects" that could also account for the regional variation we observed in our samples.…”
supporting
confidence: 92%
“…The proportion of ERα positive breast cancer incidence relative to the total diagnoses is similar for patients in the United States and Northern Israel 86,87 ; however, our data suggest that ERβ positive cancer incidence may be more regionally localized. Other studies have reported high variability of ERβ expression in laryngeal cancer samples, similar to the trends we observed in our samples 88 . It is important to note that although western blots were conducted in a centralized lab, our samples were originally fixed and processed at two different institutions, which could have caused "batch processing effects" that could also account for the regional variation we observed in our samples.…”
supporting
confidence: 92%
“…The paucity of literature on female HNCs is due to low female case numbers available at each individual institution, low female HNC incidence, and a lack of standardized reproductive or hormone use data collection on HNC patients in general . However, estrogen hormone receptors have been shown to be functional in HNC cell lines, expressed depending on hormone ligand stimulation , and, recently, correlated with HNC survival status . However, the role of hormones in head and neck carcinogenesis in a human model remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck malignant carcinoma is a commonly diagnosed cancer and its incidence has risen over the past decade (1). Oral squamous cell carcinoma (OSCC) is an important oral malignancy, accounting for >90% of head and neck malignant carcinoma cases (2).…”
Section: Introductionmentioning
confidence: 99%